Kajian Penggunaan Antibiotik pada Pasien Meningitis dan Ensefalitis Bakteri di Bangsal Rawat Inap Rumah Sakit Rujukan Utama - Diyan Ajeng Rossetyowati; Ika Puspitasari; Tri Murti Andayani; Titik Nuryastuti (Pharmacon: Jurnal Farmasi Indonesia, 2021)
Inadequate antibiotic therapy for meningitis and bacterial encephalitis is one of the factors that can jeopardize patient safety and turn into a public health issue in a number of nations, including Indonesia. This phenomena has the potential to raise health-care expenses, which should be avoided in the era of the JKN program's implementation. The goal of this research was to describe the profile of antibiotic use and cost in hospitalized meningitis and bacterial encephalitis patients. This cross-sectional observational study took place from January to December 2019. As study materials, patient medical records and billing data were employed. To enhance the data obtained, confirmation with medical and pharmaceutical personnel is required. Antibiotic use and expenditures were described using descriptive analysis. A total of 71 patients, both children and adults, met the study's inclusion criteria. Antibiotics were given to all of the patients, and the results revealed that third generation cephalosporins (49.375%) were the most commonly recommended antibiotic class, either alone or in combination. Antibiotic use receives 46.94% of total medication funding. According to the length of stay category, the majority of patients (45.99 %) were hospitalized for 8-14 days consecutively with antibiotic medication. Antibiotics, which are typically administered to patients with meningitis and bacterial encephalitis, had no effect on the length of stay in the hospital. Antibiotic prescriptions must be carefully reviewed at top referrel hospital, taking into account the local germ map.